Increased Environment-Related Metabolism and Genetic Expression in the In Vitro Matured Mouse Oocytes by Transcriptome Analysis - Zhang, Hao-Lin; Xu, Yi; Ju, Jia-Qian; Pan, Zhen-Nan; Liu, Jing-Cai; Sun, Shao-Chen (Frontiers in Cell and Developmental Biology, 2021)
Infertility is a world-wide problem for the human at reproductive age, and oocyte in vitro maturation (IVM) is generally applied to acquire the embryo in assisted reproductive technology (ART) for this issue. However, it is still unclear for the differences of RNA expression profile in the oocytes between in vivo (IVO) and IVM culture environment. In this study, we compared the global RNA transcription pattern of oocytes from in vitro and in vivo maturation in mouse. Our results showed that 1864 genes differentially expressed between the IVO and IVM oocytes. Among these 1638 genes were up-regulated and 226 genes were down-regulated, and these changes were mainly divided into environmental adaption, metabolism and genetic expression. Our detailed analysis showed that the expression of genes which belong to metabolism-related processes such as energy metabolism, nucleotide metabolism and carbohydrate metabolism was changed; and these genes were also belonged to organismal systems including environmental adaptation and circulatory system; moreover, we also found that the relative gene expression of genetic expression processes, such as protein synthesis, modification, and DNA replication and repair were also altered. In conclusion, our data suggest that in vitro maturation of mouse oocyte resulted in metabolism and genetic expression changes by environmental changes compared with in vivo matured oocytes.